Helicobacter pylori Suppresses Serum Immunoglobulin Levels in Smokers with Peptic Ulcer: Probable Interaction Between Smoking and H. pylori Infection in the Induction of Th1 Predominant Immune Response and Peptic Ulceration - Matsukawa, Yoshihiro; Kato, Kimitoshi (IntechOpen, 2011)
None